The Effect of Atypical Nucleic Acids Structures in DNA Double Strand Break Repair: A Tale of R-loops and G-Quadruplexes - Camarillo, Rosa; Jimeno, Sonia; Huertas, Pablo (Frontiers in Genetics, 2021)
The fine tuning of the DNA double strand break repair pathway choice relies on different regulatory layers that respond to environmental and local cues. Among them, the presence of non-canonical nucleic acids structures seems to create challenges for the repair of nearby DNA double strand breaks. In this review, we focus on the recently published effects of G-quadruplexes and R-loops on DNA end resection and homologous recombination. Finally, we discuss previously published data and unpublished recent results from our lab that suggest a connection between the repair over those two atypical DNA structures.